温庭筠艳情诗词研究 = Study on Wen Tingyun’s erotic poetry and Ci-poetry - 洪媛 Hong, Yuan (2015)
艳情诗在南朝时期兴盛，与当时盛行的宫体诗合流。到了晚唐时期，艳情风格的作品则又达到了新的高度，晚唐大家李商隐、杜牧等皆有大量优秀诗作。同时期的温庭筠不仅致力于艳情诗的创作，作为开一代“侧艳”词风的“花间鼻祖”，温庭筠对词的发展更做出了突出的贡献。他有意区分诗体与词体，并规范了词的长短句格律形式。他鲜明标榜艳情文学主张，奠定了文人词绮丽香艳的风格类型，开创了婉约的词风。论文共分五个部分。绪论部分对艳情文学的发展作简要的阐述，并概述相关文献研究与选题意义。第一章主要分析温庭筠诗词纤艳和疏朗两大艺术风格特色，并比较清新疏朗诗词的异同。第二章对比温庭筠艳情诗词并探讨其诗词的离合，以此论述温庭筠艳情诗词在意象、语言和境界上都具有对美的追求，而在空间呈现、女性形象和情感表达上又具有开闭、内外和简繁之分。诗词的合表现在诗蕴词情，词渗诗意，情感表达和诗词境界的差异则体现了诗词的离。第三章纵观南朝宫体诗到晚唐花间词的艳情文学沿革，探讨晚唐时期在诗为主流文体的环境下，温庭筠对文体转换的完成与影响，探究其对词体和词境的开拓和贡献，定义温庭筠在诗词史上的地位。结语部分将总结前文所讨论的重点，从而说明温庭筠在诗词史具有承前启后的重要地位。Erotic poetry was flourished and prevailing with the form of Palace (Gong Ti) Poetry in Southern Dynasties. In the late Tang Dynasty, erotic poetry move into another high tide. There are many representative poets such as Li Shangyin, Du Mu who had produced excellent erotic poems. Wen Tingyun was an eminent poet as well, but he was not only committed to erotic poetry writing, and he was also the originator of Huajian Ci-poetry. Wen Tingyun has made significant contributions to the development of Ci-poetry. He intends to distinguish Ci-poetry from poetry, and standardizes the format of Ci-poetry. He promoted erotic literature and established flowery and gorgeous style for Ci-poetry. The thesis consists of five parts. The introduction would give an overview to the development of erotic literature from Han Dynasty to late Tang Dynasty, and a brief explanation to the significance of choosing this topic, based on the comprehensive related literature review. Chapter one analyzes the characteristics of two writing styles by Wen Tingyun, which are gorgeous and elegant, as well as compare non-erotic poems with Ci-poetry. Chapter two is the main part of this thesis, which focuses on comparison between erotic poetry and Ci-poetry, to conclude similarities in the imagery, language and the artistic conception. The differences are about the presentation of space, the female image and emotional expression. The second chapter would also discuss the internal relations between Wen Tingyun’s poetry and Ci-poetry writing. Chapter three makes a summary on the progress of erotic literature based on the change of writing format from poetry to Ci-poetry. Wen Tingyun, as the first poet in Chinese literary history to devote himself to the writing of Ci-poetry, had deconstructed the tradition of classical Chinese poetics and achieved the transition from erotic poetry to Ci-poetry. He had pioneered and founded the aesthetic style with full of the erotic magnificence for Ci-poetry writing, Last but not least, the conclusion summarizes the findings of the thesis, which demonstrate that Wen Tingyun’s contribution in development of Ci-poetry is remarkable and significant.